무역업체의 AEO 인증이 생산성 및 효율성에 미치는 영향 - 전동화(Dong-Hwa Jeon), 구종순(Jong-Soon Koo), 황수정(Su-Jung Hwang) (무역연구, 2016)
This study aims to investigate the effect of AEO certification on the productivity and efficiency of trading firms in Korea. We evaluated 162 selected sample firms by using Malmquist Productivity Index from 2009 to 2015, and after that, conducted panel regression to scrutinize the effect of AEO certification on these productivity changes. According to the results, AEO certification positively affects productivity and efficiency changes, but it negatively affects technical change. Futhermore, we found that these AEO certification effects are somewhat different depending on firm size. AEO certification is significant and strongly affects more the productivity of small-and medium-sized firms, compared to large-sized firms. Based on the results, we conclude that AEO certification affects firm productivity changes, efficiency changes and technical changes. Through AEO certification, trading firms can improve their productivity and efficiency by attaining, their benchmarks on an efficient production frontier line. However, additional costs to meet AEO certification requirements may curtail their production possible area. KCI Citation Count: 3